COMUNICAÇÃO NA TRANSIÇÃO DE CUIDADOS DE ENFERMAGEM EM UM SERVIÇO DE EMERGÊNCIA DE PORTUGAL - Cidália Maria da Cruz Silva Patacas de Castro; Maria do Céu Mendes Pinto Marques; Célia Rodrigues de Oliveira Tavares de Vaz (Universidade Federal do Paraná, 2022)
Objective: to identify nurses' opinions about the transition of care at shift change in the emergency department and understand their knowledge about patient safety. Method: quantitative, descriptive, cross-sectional study, conducted in January 2019, in an emergency department of a hospital in the metropolitan area of Lisbon, Portugal. Non-probability convenience sample with 50 nurses. Data analysis used descriptive and inferential statistics, with the Mann-Whitney test. Results: information transmitted is updated (80%); there is noise that interferes with the transmission of care (84%); patient assessment in the transition of care is beneficial (84%). 50% know the international goals for patient safety; 84% agree that the ISBAR methodology contributes to patient safety. Conclusion: it is evident the formation of professionals and the use of standardized instruments as fundamental strategies for patient safety in the transition of care.